Telaah Moshing sebagai Bentuk Ekspresi Pemuda pada Komunitas Musik Hardcore di Malang Raya - Azzam, Shidqii Abdullah; Meiji, Nanda Harda Pratama (Universitas Gadjah Mada, 2023)
Body movements such as brawls, playing with hands and feet, pushing bodies between actors, and cases of death have been found, causing moshing to be viewed negatively, particularly by commoner. Using a phenomenological approach as well as a youth study approach in the form of an emic approach, this research seeks to answer ignorance about the background of moshing and understand moshing as a form of communication for young survivors of hardcore music. According to the findings, there were several types of moshing, including two-step, violence dance, wall of death, stage dive, crowd killer, and pogo, which have also been classified as positive or negative hardcore based on the background of each hardcore band. Moshing was able to provide free space in expressing moods when there were problems, feeling bored and tired after full activities; a place for having fun to vent negative aura into positive aura; and excess inner satisfaction in enjoying hardcore music for youth in Malang City. As a result, if people position themselves as the perpetrator, moshing did not always become a negative thing.